Artificial Intelligence: A New Era in Drug Discovery - Mishra, Devendra Kumar; Awasthi, Himani (Asian Journal of Pharmaceutical Research and Development, 2021)
Artificial intelligence (AI) is a simulation of the process of human intelligence through computers. The process involves obtaining information, developing rules for using information, making possible or accurate conclusions, and self-correcting. The development of new drug residues begins when basic scientists learn about biological targets (receptor, enzyme, protein, and gene). These targets involve the biological processes that occur in patients with a disease. Drug discovery can be through target identification, target verification, lead identification, and effectiveness of lead. AI can offer revolutionary insights into medicine, through data from genetics, proteomics and other life sciences that advance the process of discovery and development. Artificial Intelligence (AI) has recently been developed as a fiery element in the medical care industry. AI has exciting potential for prosperity in the field of biopharmaceutical. The biopharmaceutical industry makes efforts to approach AI to improve drug discovery, reduce research and development costs, reduce the time and cost of early drug discovery, and support predicting potential risks/side effects in late trials that can be very useful in avoiding traumatic events in clinical trials and ultimately clinical trials. Usually, drug development takes five years to go to trial, but the AI drug takes just 12 months. The rapid growth in life sciences and machine learning algorithms has led to enormous statistical access to the growth of AI-based startups focused on drug innovation in recent years.